2023
DOI: 10.1161/strokeaha.123.042691
|View full text |Cite
|
Sign up to set email alerts
|

Early Recanalization Among Patients Undergoing Bridging Therapy With Tenecteplase or Alteplase

Thomas Checkouri,
Gaspard Gerschenfeld,
Pierre Seners
et al.

Abstract: BACKGROUND: Intravenous thrombolysis (IVT) with alteplase or tenecteplase before mechanical thrombectomy is the recommended treatment for large-vessel occlusion acute ischemic stroke. There are divergent data on whether these agents differ in terms of early recanalization (ER) rates before mechanical thrombectomy, and little data on their potential differences stratified by ER predictors such as IVT to ER evaluation (IVT-to-ER eval ) time, occlusion site a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Regarding study design, this meta-analysis included two RCTs [ 19 , 30 ] and eight non-randomized, non-blind cohort studies [ 16 , 23 – 29 ]. Eight used a prospective approach [ 16 , 19 , 23 25 , 27 , 28 , 30 ], while two were based on a retrospective approach [ 26 , 29 ]. Regarding review system, six were peer-reviewed studies [ 19 , 23 25 , 28 , 30 ] and four were non-peer-reviewed studies [ 16 , 26 , 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding study design, this meta-analysis included two RCTs [ 19 , 30 ] and eight non-randomized, non-blind cohort studies [ 16 , 23 – 29 ]. Eight used a prospective approach [ 16 , 19 , 23 25 , 27 , 28 , 30 ], while two were based on a retrospective approach [ 26 , 29 ]. Regarding review system, six were peer-reviewed studies [ 19 , 23 25 , 28 , 30 ] and four were non-peer-reviewed studies [ 16 , 26 , 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight used a prospective approach [ 16 , 19 , 23 25 , 27 , 28 , 30 ], while two were based on a retrospective approach [ 26 , 29 ]. Regarding review system, six were peer-reviewed studies [ 19 , 23 25 , 28 , 30 ] and four were non-peer-reviewed studies [ 16 , 26 , 27 , 29 ]. The largest sample was included in the study by Checkouri et al (n = 1865) [ 28 ], while Marín et al [ 29 ] had the smallest (n = 18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early trials supported these claims with higher recanalization rates [29], but some later studies demonstrated non-inferiority [30,31]. A new study has just demonstrated that TNK may be 2.4-times more effective for early recanalization of thrombi longer than 10 mm in comparison to TPA [32], highlighting how physical clot characteristics may determine the drug choice. Due to time restrictions, only 3-8% of patients are eligible for intravenous clot lysis.…”
Section: Clot Lysismentioning
confidence: 99%